Global DNA methylation status in laryngeal cancer. Issue 3 (1st June 2013) - Stembalska, Agnieszka; Leszczyński, Przemysław; Gil, Justyna; Ramsey, David; Pitala, Grzegorz; Maciejczyk, Adam; Frączek, Marcin
<x xml:space="preserve">Abstract</x> Background The purpose of our study was to evaluate if DNA methylation level in leukocytes may be used as a surrogate marker of genome methylation status in laryngeal cancer tissues. Methods We evaluated global DNA methylation using an ultra performance liquid chromatography (UPLC)‐based method to assess the total content of 5‐methylcytosine (5 mC). Results The study was performed on DNA isolated from cancer tissues, adjacent normal tissues, and peripheral blood leukocytes in a group of 72 patients with laryngeal cancer. DNA hypomethylation was found in tumor tissue (56%) and normal tissue (49%). There was a significant correlation between the levels of 5 mC in these 2 types of tissue. There was no significant DNA hypomethylation in blood. A negative correlation between tumor grade and blood levels of 5 mC was found. Conclusion The level of leukocyte DNA methylation measured using total 5 mC content cannot be used as a surrogate marker for genome methylation status in laryngeal cancer tissues. © 2013 Wiley Periodicals, Inc. Head Neck36: 419–424, 2014